ANALYSIS OF APPROACHES TO UNDERSTANDING THE CIVIL SERVICE IN THE RUSSIAN FEDERATION AND FOREIGN COUNTRIES - Ivanenko, Igor; Grin, Maksim; Zinisha, Olga; Achmiz, Asiet (Revista Inclusiones, 2020)
The article analyzes the legal norms establishing the institution of the state civil service in the Russian Federation and a series of foreign countries. In the course of the analysis, the characteristic features inherent in this institution were identified in accordance with the legislation of each of them. The significance of the study is an attempt to unify the characteristics inherent in the civil service as a legal institution for effective reform taking into account world experience.